Mechanisms of chloride modulated activity in the C-domain of angiotensin-converting enzyme - Yates, Christopher John (Division of Medical Biochemistry, 2014)
The somatic isoform of angiotensin-converting enzyme (sACE), a key regulator of blood pressure and electrolyte fluid homeostasis, primarily cleaves the hypertension-associated angiotensin-I (AngI) and bradykinin peptides, as well as a number of other physiologically relevant peptides in vitro. sACE consists of two homologous and catalytically active N- and C- domains which display marked differences in substrate specificities and chloride activation. To investigate these potential mechanisms, a series of single amino acid substitution mutants (based on analysis of aligned C- and N-domain 3D structures) were generated in a soluble, minimally glycosylated C-domain construct. Evaluation of these constructs was done using AngI and the short synthetic substrates hippuryl-L-histidyl-Lleucine (HHL) and Z-phenylalanyl-L-histidyl-L-leucine (Z-FHL) under differing chloride concentrations. An isothermal titration calorimetry-based assay was developed to determine the effect of chloride concentration on enzyme thermodynamic and kinetic parameters. Chloride binding in the chloride 1 pocket of tACE was found to affect positioning of K511 and potentially alter the conformation of the active site. This would alter C-terminal substrate interactions, which were suggested to affect chloride 2 pocket ion affinity by coordinating Y520 and affect peptide bond rotation and hence substrate interactions. The analysis of the chloride 2 pocket R522Q and R522K mutations revealed a key R522-Y523 Pi-cation interaction that is stabilized via chloride coordination of R522. Substrate interactions in the S2 sub-site were shown to affect positioning of this complex as well as chloride affinity in the chloride 2 pocket. The E403-K118 salt bridge in tACE was shown to stabilize the hinge-bending region and reduce chloride affinity by constraining the chloride 2 pocket, an interaction which is destabilized via substrate interactions within the S2 pocket which results in tighter chloride binding. This work showed that substrate composition to the C-terminal side of the scissile bond, as well as interactions of larger substrates in the S2 sub-site, moderate chloride affinity in the chloride 2 pocket of the ACE C-domain, providing a rationale for the substrate selective nature of chloride dependence in ACE and how this varies between the N- and C- domains.